Beyond These Mythical Shores: Asian American History and the Study of Race - Jung, Moon-Ho (History compass, 2008)
The field of Asian American history has witnessed a sharp increase in monograph publications since the 1990s, reflective of the field's growing recognition and sophistication. Anti-Asian racism, particularly in the form of immigration restrictions and prohibitions, continues to dominate the historical literature on Asian Americans, but historians are building on earlier calls to move the field beyond liberal narratives of immigration and assimilation. Recent publications on the nineteenth century extend the temporal and geographical scope of Asian American history and offer radical critiques of race, nation, and empire in U.S. history.